Hedging, financing, and investment decisions: A simultaneous equations framework - Chen-miao Lin; Stephen D. Smith (Federal Reserve Bank of Atlanta, 2005)
The purpose of this paper is to empirically investigate the interaction between hedging, financing, and investment decisions. This work is relevant in that theoretical predictions are not necessarily identical to those in the case where only two decisions are being made. We argue that the way in which hedging affects the firms' financing and investing decisions differs for firms with different growth opportunities. We empirically find that high-growth firms increase their investment, but not their leverage, by hedging. However, we also find that firms with few investment opportunities use derivatives to increase their leverage.
Keywords: G31; G32; 330; investment; financing; hedging; Investitionsentscheidung; Unternehmensfinanzierung; Hedging; Simultanes Gleichungssystem